College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter 6 - Section 6.3 - Exponential Functions - 6.3 Assess Your Understanding: 85

Answer

$\dfrac{1}{4}$

Work Step by Step

RECALL: (1) $a^{-m} = \dfrac{1}{a^m}$ (2) $a^{mn}= (a^m)^n$ Note that $2x=-x(-2)$ Thus, $3^{2x} = 3^{-x(-2)}$ Use rule (2) above to obtain: $3^{-x(-2)} = (3^{-x})^{-2}$ With $3^{-x} = 2$, the expression above is equivalent to: $(3^{-x})^{-2} = 2^{-2}$ Use rule (1) above to obtain: $2^{-2} = \dfrac{1}{2^2} = \dfrac{1}{4}$ Thus, $3^{2x} = \dfrac{1}{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.